Law enforcement role in reducing road crashes - Jamil Mujahed (19807251) (2015)
Three thousand people, including 500 children, are killed every day on the world’s roads. These amounts to 1.2 million deaths a year .In addition more than 50 million people are seriously injured; many are disabled for life. According to WHO reports, the number of road crashes fatalities will increase worldwide by 60% by 2020. Road crashes represent a major social cost to most societies, and their management has thus been a high priority. Efforts in management have been at the levels of both prevention (via education, enforcement and engineering) and cure (via the hospital and insurance systems). A large proportion of road traffic crashes are as a result of road-user behavior and more specifically, crashes occur because of the decisions taken by road users to disobey or break the road rules, commonly referred to as human error. Crashes rates and compliance are inversely related. Law enforcement agencies like the traffic police come up with strategies including use of penalties to ensure road rules are obeyed and compliance improves. Good traffic law enforcement is essential for road safety .The main objective of law enforcement is road safety – achieved by deterring road users from committing offences, which are related to road crashes and injuries. Police activities should primarily serve as deterrence for drivers inclined to commit traffic offences through increasing road users’ perception of the risk of being caught. Consistent deterrence strategies, which typically comprise highly visible police or camera activity can bring about lasting changes in road user behavior and, as a consequence, changes in road users’ attitudes which reinforce these behavioral changes. It is generally accepted that enforcement influences driving behavior through two processes: general deterrence and specific deterrence. Enforcement of road rules should be aimed primarily at causing general deterrence because then it is not necessary for police to catch and punish road users for them to be encouraged to obey the rules. To result in general deterrence, enforcement should be: accompanied by publicity, unpredictable and difficult to avoid, a mix of highly visible and less visible activities, and continued over a long period of time. Targeted and appropriate legislation that is consistently enforced and well understood by the public is a critical component of successful enforcement. An appropriate penalty system also needs to be in place. In many cases road users do not obey traffic laws and regulations because they do not know them .yet, even when people know the rules they do not obey them .while public education programs are important in informing the general public – especially if new laws and regulations are introduced – enforcement is important if some level of compliance is to be achieved. It should be recognized that not all enforcement should involve punishment. Some enforcement activity can be aimed at offering positive feedback, or reward, or offering education and courses in improved driving, rather than a fine. Other Information Published in: Journal of Local and Global Health Science, title discontinued as of (2017) License: https://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.5339/jlghs.2015.itma.90